A case analysis of service‐member trauma processing related to art therapy within a military‐intensive outpatient program. Issue 9 (17th January 2020) - Maltz, Brenda; Hoyt, Tim; Uomoto, Jay; Herodes, Megan
Abstract: Objectives: Art therapy has been widely used in clinical settings and has shown preliminary success in military trauma. This case study describes a mask‐making art therapy directive facilitated by a board‐certified art therapist as an adjunct to group posttraumatic stress disorder (PTSD) treatment in a military‐intensive outpatient program. Methods: Described are clinical outcome measures, linguistic analysis of a personal journal, evaluation of this service‐member's artwork, and experiences in the program. Results: Mask‐making, as a trauma‐focused group‐art therapy directive, expanded the understanding of treatment progress reflected in journal notes, mask imagery, and by a change in linguistic indices of trauma processing, despite an overall increase in PTSD symptoms as he confronted his traumatic experiences. He reported improvement in coping and successfully returned to full military duty following treatment. Conclusions: This case study suggests that art therapy and written narrative, combined with standardized self‐report assessments, may more accurately indicate improvement in overall PTSD treatment.